Pendekatan Pembelajaran Kontekstual Pengaruhnya Terhadap Aktivitas Belajar Peserta didik - Sirajuddin Saleh; Syamsurijal Basri; Sumarlin Mus (Universitas Negeri Makassar, 2022)
This study aims to determine the description of the teacher's contextual learning approach, student learning activities, and the effect of the contextual learning approach on student learning activities. To achieve this goal, research data were collected using observation, questionnaires, and documentation. The total population of the study was 151 students and a sample of 75 students. The data were analyzed using descriptive statistical analysis of percentages and inferential statistical analysis through product-moment correlation test and simple linear regression analysis. The results showed that the description of the use of the contextual learning approach was in the high category and the learning activities of students were in the very high category. The results of hypothesis testing indicate that there is a positive and significant influence between the contextual learning approach to the active learning of students. Thus, it can be understood that the contextual learning approach makes a positive and significant contribution in increasing students' learning activities.